ESTIMATON OF MAXIMUM SHORT-TERM PRECIPITATION OVER THE RIJEKA REGION (Advances in Civil and Architectural Engineering, 2021)
In this paper, we considered the occurrence of extreme short-term rainfall in the region of Rijeka city, analyzed the extreme values, and commented on application of the results. We estimated the maximum precipitation amounts for different occurrence probabilities (return periods) for time intervals of 5, 10, 20, 30, 40, and 60 minutes, as well as 2, 4, 8, 12 and 24 hours, using data taken at the Rijeka meteorological station over periods of 1958–2011 and 1958–2012. Additionally, we evaluated the extremity of a heavy rainfall event that affected the city of Rijeka on September 12th, 2012. Using absolute extremes recorded for time intervals of 20 minutes to 2 hours, we accounted for precipitation peaks to calculate new intensity–duration–return period curves for Rijeka. In this way, we revised the precipitation input parameters used to plan and design urban drainage systems. This revision included significant changes for durations of 20, 30, and 40 minutes, for which the amounts recorded on September 12th, 2012 had return periods of longer than 100 years.